Effectiveness of clinical abdominal scoring system in the management of patients with blunt trauma abdomen - Kumar, Dharmendra; K., Mohan Kumar (International Surgery Journal, 2021)
Background: Abdominal injury being the most common cause of mortality and morbidity, its incidence comes after extremities and head injury. Early diagnosis and treatment can reduce mortality by upto 50%. The common causes for blunt trauma abdomen include motor vehicle crashes, direct trauma and fall from heights. Objectives of the current investigation were to score the patients with BTA with clinical abdominal scoring system and to compare the score of CASS with USG/CT abdomen and pelvis findings in patients of BTA. Methods: All patients who are suspected to have BTA were scored using CASS and radiological investigations were done in the ED. The decision to proceed with the surgery would be done if the patient had CASS >12 and/or if the radiological investigation shows features of BTA like air under diaphragm or grade IV/V solid organ injury. Results: Males accounts for 81% of cases and the rest being females. Most common mode of injury was found to be RTA. Most common injured organs are spleen >liver >small intestine (ileum). The CASS has specificity of 84.62%, sensitivity of 99.2%, PPV 33.3%, NPV 100%. Total mortality in the study was 7.1% Conclusions: Patients with CASS of <8 can be managed conservatively. Patient with score >12 or hemodynamically unstable can be taken up for emergency laparotomy without any delay. Patients with CASS between 9 and 11, with good clinical assessment aided with radiological investigations can be managed depending upon the severity of the injury.